Neutropenia and Neutropenic Complications in ABVD Chemotherapy for Hodgkin Lymphoma - Bhanu Vakkalanka; Brian K. Link (Advances in Hematology)
A combination of Adriamycin (a.k.a. Doxorubicin), Bleomycin, Vinblastine, and Dacarbazine (ABVD) is the most commonly used chemotherapy regime for Hodgkin lymphoma. This highly effective treatment is associated with a significant risk of neutropenia. Various strategies are adopted to counter this commonly encountered problem, including dose modification, use of colony stimulating factors, and prophylactic or therapeutic use of antibiotics. Data to support these approaches is somewhat controversial, and in keeping with the paucity of definitive evidence, there is a wide disparity in the management of neutropenia in patients receiving ABVD chemotherapy. This paper summarizes the evidence for managing ABVD-related neutropenia during the treatment of Hodgkin lymphoma.